Criteria used by venture capitalists: a cross country analysis - Knight, Russell; Gilbertson, David (School of Management Working Papers, 1993)
This paper describes a cross cultural survey of international venture capitalists to investigate the criteria they use to evaluate venture proposals. The criteria were taken from a U.S. survey of venture capital firms and the results are compared and contrasted with the original U.S. responses. The study was done in Canada and the Asia Pacific region and the responses are compared to study differences and similarities between responses from various regions. The similarities of responses are quite striking, although several differences are apparent, such as the difference in emphasis on high technology.